Catalytic gasification of lignite in supercritical water with Ru/CeO2–ZrO2. (2nd March 2016) - Yu, Jiangdong; Lu, Xiuyun; Shi, Yunjie; Chen, Qiuling; Guan, Qingqing; Ning, Ping; Tian, Senlin; Gu, Junjie
Abstract: A series of CeO2 –ZrO2 (CZ) supported Ru catalysts were prepared and employed to catalytic gasification of lignite in supercritical water (SCW). The influences of Ru content, catalyst loading, reaction temperature and feed concentration on gasification of lignite were investigated. Results indicated that Ru2 /CZ shows high activity for gasification of lignite and hydrogen production. At 500 °C and 17 min with a 2 wt% loading of lignite and a 2 g/g catalyst loading, carbon gasification efficiency about 86% has been achieved and the highest H2 yield (29.24 mol/kg) has been produced, representing nearly 21-fold enhancement of yield compared to that in the noncatalytic case. The kinetic study in terms of overall reaction rate was investigated and the activation energy Ea is 130 ± 26 kJ/mol. Furthermore, catalyst recycling experiments were conducted in order to evaluate the stability of Ru2 /CZ catalyst. The results and XPS data indicate that ZrO2 enhance the stability of the catalyst. Thus, the Ru2 /CZ catalyst seems to be a promising material for SCWG of lignite for gas fuels, especially for hydrogen. Highlights: Lignite have been effectively gasified in supercritical water using Ru/CeO2 –ZrO2 . The H2 production is improved and stability of CeO2 is enhanced by introducing Zr 4+ into CeO2 . Higher than 85% carbon gasification efficiency achieved in a moderate temperature 500 °C.